Power Quality Improvement by Unified Power Quality Conditioner Based on CSC Topology Using Synchronous Reference Frame Theory - Dharmalingam, Rajasekaran (Hindawi Publishing Corporation, 2014)
This paper deals with the performance of unified power quality conditioner (UPQC) based on current source converter (CSC) topology. UPQC is used to mitigate the power quality problems like harmonics and sag. The shunt and series active filter performs the simultaneous elimination of current and voltage problems. The power fed is linked through common DC link and maintains constant real power exchange. The DC link is connected through the reactor. The real power supply is given by the photovoltaic system for the compensation of power quality problems. The reference current and voltage generation for shunt and series converter is based on phase locked loop and synchronous reference frame theory. The proposed UPQC-CSC design has superior performance for mitigating the power quality problems.